Mitochondrial uncoupling protein may participate in futile cycling of pyruvate and other monocarboxylates - Jezek, P; Borecký, J (The American journal of physiology, 1998)
The physiological role of monocarboxylate transport in brown adipose tissue mitochondria has been reevaluated. We studied pyruvate, alpha-ketoisovalerate, alpha-ketoisocaproate, and phenylpyruvate uniport via the uncoupling protein (UCP1) as a GDP-sensitive swelling in K+ salts induced by valinomycin or by monensin and carbonyl cyanide-p-(trifluoromethoxy)phenylhydrazone in Na+ salts. We have demonstrated that this uniport is inhibited by fatty acids. GDP inhibition in K+ salts was not abolished by an uncoupler, indicating a negligible monocarboxylic acid penetration via the lipid bilayer. In contrast, the electroneutral pyruvate uptake (swelling in ammonium pyruvate or potassium pyruvate induced by change in pH) mediated by the pyruvate carrier was inhibited by its specific inhibitor alpha-cyano-4-hydroxycinnamate but not by fatty acids. Moreover, alpha-cyano-4-hydroxycinnamate enhanced the energization of brown adipose tissue mitochondria, which was monitored fluorometrically by 2-(4-dimethylaminostyryl)-1-methylpyridinium iodide and safranin O. Consequently, we suggest that UCP1 might participate in futile cycling of unipolar ketocarboxylates under certain physiological conditions while expelling these anions from the matrix. The cycle is completed on their return via the pyruvate carrier in an H+ symport mode.
Keywords: kyseliny karboxylové; kinetika; Rotenone; Monensin; biologický transport; membránové proteiny; lipidové dvojvrstvy; zduření mitochondrií; Adipose Tissue, Brown; Carbonyl Cyanide p-Trifluoromethoxyphenylhydrazone; křečci praví; mitochondrie; Membrane Proteins; iontové kanály; Carrier Proteins; Uncoupling Protein 1; koncentrace vodíkových iontů; Biological Transport; křeček rodu Mesocricetus; valinomycin; Guanosine Diphosphate; guanosindifosfát; Phenylpyruvic Acids; Lipid Bilayers; karbonylkyanid-p-trifluormethoxyfenylhydrazon; Mesocricetus; pyruváty; Mitochondrial Proteins; kyseliny kumarové; zvířata; Mitochondrial Swelling; Carboxylic Acids; Hydrogen-Ion Concentration; kyseliny fenylpyrohroznové; Pyruvates; Valinomycin; uncoupling protein 1; rotenon; Kinetics; Mitochondria; Cricetinae; Ion Channels; Coumaric Acids; hnědá tuková tkáň; monensin; transportní proteiny; mitochondriální proteiny; Animals